Tradisi Lokal sebagai Urf Progresif - MN Harisudin (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2007)
For some, Western culture is not only a form of civilization? par? excellencebut also a culture that is immune from any critique. Still for some, Western culture is a high culture while other cultures are low cultures. Furthermore, post-colonial studies maintain that Western culture occupies the centre of human civilization while other cultures are at the periphery. The thrust of this latter view is that the Western culture may dominate and rule other cultures. Hence, the real nature of the Western culture is that of hegemony. Now, Western culture has been manifested in many habits and traditions such as pornography, homosexuality, and other form of cultural identity which are malevolent in their nature. In this regard, this paper is interested to show that ?Urf (local custom) as a framework of analysis commonly used by the scholars of Islam can be appropriated to challenge the hegemonic view of the Western culture and to prove that in fact Western culture can occupy not the centre of human civilization but the periphery.